Development and Standardization of Household Food and Nutritional Security Index - Jairu, Dristika; Chauhan, Amardeep; Kameswari, V.L.V. (Indian Journal of Extension Education, 2023)
An assessment of Household Food and Nutritional Security (HFNS) is important to understand the nutritional state of a household. There are various techniques available for measuring it but they are all in scattered form, making the study tedious. Present research carried out during 2022-23 was aimed at constructing a composite HFNS index, that would aid in amalgamating the different techniques to holistically study the HFNS. Initially, four dimensions and 48 indicators were identified and subjected to relevancy testing through judges' opinions which resulted in the selection of 32 indicators. A questionnaire with finalized indicators was administered to 60 households in the non-sampling area. The test-retest and split-half method was followed for testing the reliability of the tool and the reliability co-efficient was 0.84 and 0.87, respectively. Content validity and statistical validity were used to confirm the validity of the tool which was 0.96. The developed tool finally consisted of four dimensions and 32 indicators which are reliable and can produce consistent results while assessing the food and nutritional security of rural households.